The Influence of Occupational Health and Safety (K3) Culture, Work Environment and Competence on Employee Performance of PT. Halmahera Persada in South Halmahera - Kristiyanto, Dian; Khaerudin, Khaerudin (Dinasti Publisher, 2025)
In this study, the author will analyze the influence of Occupational Safety Culture on employee performance and job satisfaction through a quantitative approach using interview methods and content analysis. This study focuses on the relationship between manpower, work methods, behavior, competence, and work safety programs. Through in-depth analysis of data, interviews, and field observations on employees of PT. Halmahera Persada in South Halmahera. Data collection techniques by filling out questionnaires by sample respondents of 60 employees taken from a population of 623 employees. Furthermore, answers through closed questions by choosing one of the appropriate answers according to respondents on a rating scale of one (strongly disagree), two (disagree), three (neutral), four (agree), and five (strongly agree). The results prove that there is a direct influence of occupational safety and health, work environment, and competence on employee job satisfaction and performance, and there is an indirect influence of occupational safety and health through positive job satisfaction significantly on employee performance but does not have an impact on employee performance, because the value of the influence is smaller than the direct influence.